2016
DOI: 10.1007/s00213-016-4427-2
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive temperament predicts ethanol self-administration in late adolescent male and female rhesus macaques

Abstract: Rationale Anxiety and aggression are associated with ethanol self-administration, but these behaviors can serve as either risk factors for or consequences of heavy drinking in rodents and humans. Baseline levels of aggressive-like and anxious-like behavior in non-human primates have not yet been characterized in relation to future or prior ethanol intake. Objective To test the association between temperament at baseline with future ethanol self-administration in late adolescent male (n=21) and female (n=11) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…These temperaments can be viewed as endophenotypes with genetic basis towards development of alcohol use disorders (McClintick and Grant, 2016) and temperament can predict adolescent alcohol use in humans (Dick et al, 2013). Monkeys also exhibit stable temperaments that can be quantified when confronted with strangers or novel objects, by the degree of behavioral inhibition (anxious animals) or aggressive responses (aggressive animals) (Kalin and Shelton, 1989).…”
Section: Ii: Assessment Of Risks For Heavy Drinking and Stress Interamentioning
confidence: 99%
See 2 more Smart Citations
“…These temperaments can be viewed as endophenotypes with genetic basis towards development of alcohol use disorders (McClintick and Grant, 2016) and temperament can predict adolescent alcohol use in humans (Dick et al, 2013). Monkeys also exhibit stable temperaments that can be quantified when confronted with strangers or novel objects, by the degree of behavioral inhibition (anxious animals) or aggressive responses (aggressive animals) (Kalin and Shelton, 1989).…”
Section: Ii: Assessment Of Risks For Heavy Drinking and Stress Interamentioning
confidence: 99%
“…Monkeys also exhibit stable temperaments that can be quantified when confronted with strangers or novel objects, by the degree of behavioral inhibition (anxious animals) or aggressive responses (aggressive animals) (Kalin and Shelton, 1989). In a recent study, a group of 21 male and 11 female rhesus monkeys in the late adolescent/early adult stage of life were typed for temperament prior to being induced to drink alcohol (McClintick and Grant, 2016). The monkeys with aggressive temperaments self-administered more alcohol and attained higher BECs than non-aggressive monkeys.…”
Section: Ii: Assessment Of Risks For Heavy Drinking and Stress Interamentioning
confidence: 99%
See 1 more Smart Citation
“…Individual differences in stress and anxiety responses (Dilleen et al, 2012; Jimenez and Grant, 2017), social dominance (Morgan et al, 2002; Covington and Miczek, 2005), aggressive temperament (McClintick and Grant, 2016), preference for saccharine (Carroll et al, 2002), sensation or novelty seeking (Suto et al, 2001; Nadal et al, 2002; Belin et al, 2011; Flagel et al, 2014), impulsivity (Perry and Carroll, 2008; Verdejo-Garcia et al, 2008; Dalley et al, 2011), and sensitivity to rewards (Belcher et al, 2014) have all been found in both animal models and clinical studies in humans to be associated with addiction vulnerabilities, and in particular with the likelihood to develop and maintain addiction, or to resist to treatment (Piazza et al, 1989; Belin et al, 2016; Everitt and Robbins, 2016). However, investigations into the mechanisms underlying this phenotypic differentiation in addiction has so far revealed few neural or computational candidates, which are found associated with diverse and dissociable behavioral traits.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the emotional and physical signs of ethanol withdrawal include anxiety, irritability, mood swings, insomnia, tremors, convulsions, higher blood pressure, accelerated pulse, accelerated breathing, accelerated heart rate, dehydration, and delirium tremens (Schuckit et al, 1995, Finn and Crabbe, 1997). The emotional symptoms of ethanol dependence, including anxiety-like behavior and depression-like behavior, can be modeled in animals during ethanol dependence (Pleil et al, 2015, Marcinkiewcz et al, 2015, Thorsell et al, 2007, Varlinskaya et al, 2017, Kallupi et al, 2014, Gilpin et al, 2012, Gilpin et al, 2015, Heilig et al, 2010, Kliethermes et al, 2004, Pandey et al, 2015, Pandey et al, 2003, Valdez et al, 2004, Valdez et al, 2002a, Ehlers et al, 2013, Vetreno et al, 2016, Rylkova et al, 2009, McClintick and Grant, 2016, Egli et al, 2012, Buck et al, 2014). An important challenge for preclinical researchers is the fact that these tests are usually not repeatable within subjects over time, which prevents conducting reliable longitudinal studies.…”
Section: Introductionmentioning
confidence: 99%